Differential requirement of Hippo cascade during CTNNB1 or AXIN1 mutation-driven hepatocarcinogenesis - Liang, Binyong; Wang, Haichuan; Qiao, Yu; Wang, Xue; Qian, Manning; Song, Xinhua; Zhou, Yi; Zhang, Yi; Shang, Runze; Che, Li; Chen, Yifa; Huang, Zhiyong; et al. (Hepatology (Baltimore, Md.), 2023)
Background and Aims: Gain-of-function (GOF) mutations of CTNNB1 and loss-of-function (LOF) mutations of AXIN1 are recurrent genetic alterations in hepatocellular carcinoma (HCC). We aim to investigate the functional contribution of Hippo/YAP/TAZ in GOF CTNNB1 or LOF AXIN1 mutant HCCs. Approach and Results: The requirement of YAP/TAZ in c-Met/β-Catenin and c-Met/sgAxin1-driven HCC was analyzed using conditional Yap, Taz, and Yap;Taz knockout (KO) mice. Mechanisms of AXIN1 in regulating YAP/TAZ were investigated using AXIN1 mutated HCC cells. Hepatocyte-specific inducible TTR-CreERT2 KO system was applied to evaluate the role of Yap;Taz during tumor progression. Cabozantinib and G007-LK combinational treatment were tested in vitro and in vivo. Nuclear YAP/TAZ was strongly induced in c-Met/sgAxin1 mouse HCC cells. Activation of Hippo via overexpression of Lats2 or concomitant deletion of Yap and Taz significantly inhibited c-Met/sgAxin1 driven HCC development, whereas the same approaches had mild effects in c-Met/β-Catenin HCCs. YAP is the major Hippo effector in c-Met/β-Catenin HCCs, and both YAP and TAZ are required for c-Met/sgAxin1-dependent hepatocarcinogenesis. Mechanistically, AXIN1 binds to YAP/TAZ in human HCC cells and regulates YAP/TAZ stability. Genetic deletion of YAP/TAZ suppresses already formed c-Met/sgAxin1 liver tumors, supporting the requirement of YAP/TAZ during tumor progression. Importantly, tankyrase inhibitor G007-LK, which targets Hippo and Wnt pathways, synergizes with cabozantinib, a c-MET inhibitor, leading to tumor regression in the c-Met/sgAxin1 HCC model. Conclusions: Our studies demonstrate that YAP/TAZ are major signaling molecules downstream of LOF AXIN1 mutant HCCs, and targeting YAP/TAZ is an effective treatment against AXIN1 mutant human HCCs.